(untitled) (Communications in Computational Chemistry, 2025)
Density functional theory (DFT) calculations were performed to elucidate the reaction mechanism of the Pd-catalyzed carbonylation of propargylic alcohol (1), leading to the efficient synthesis of cyclohexyl α-methylene-β-lactone (2). Our study revealed that the reaction proceeds through a four-step pathway: alkyne migration and insertion, CO insertion, HCl-assisted hydrogen transfer, and final C–O annulation. Notably, the final C–O annulation step was identified as the rate-determining step (RDS) of the overall catalysis, with a free energy barrier of 25.7 kcal/mol (i.e., IM4→TS4). Additionally, we uncovered the critical role of the HCl during the reaction pathway, a demonstrating that it acts as a co-catalyst, proton shuttle, and hydrogen bond donor/acceptor. NBO, EDA-NOCV, and HIGM analyses further revealed that the remarkable stability of the transition state TS3 in the presence of HCl primarily arises from strong electrostatic attraction and orbital interaction energies between the two interacting fragments. These mechanistic insights provide valuable insight and guidance for the rational design of new Pd-catalyzed transformations.